SERVICE EVALUATION OF DEMENTIA SCREENING IN OLDER INPATIENTS. Issue 10 (9th September 2014) - Galtrey, Clare M; Daniel, Patricia; White, Sarah Jane; Lee, Chooi; Isaacs, Jeremy D
Abstract : Introduction: Since April 2012, acute hospitals need to screen older inpatients for dementia. We investigated whether investigation of low Abbreviated Mental Test (AMT) scores conforms to NICE guidance on dementia (CG42). We also evaluated inpatient experience of cognitive testing. Methods: Structured interviews with 25 inpatients who remembered their memory test. Notes review of 40 inpatients aged ≥65 without known dementia with AMT <9/10. Results: Patients accepted AMT administration and it did not cause distress. However, no patient received an explanation for the test and the majority were not given the result. Of 40 patients with AMT<9/10, 21 had collateral history documented, 18 had further cognitive testing, 30 had B12, folate and thyroid function tested. Discharge diagnoses included "dementia" (n=7), delirium (n=3), "cognitive impairment" (n=2), "confusion" (n=2), Parkinson's disease (n=2), mixed dementia (n=1), vascular dementia (n=1), multiple sclerosis (n=1). No patient was diagnosed with Alzheimer's disease. Discussion: Although memory testing is acceptable to patients, insufficient information about the test and its results is provided. Investigation of dementia falls short of NICE CG42. There is under-diagnosis of Alzheimer's disease. This suggests a gap in hospital doctors' training.